Peningkatan Kapasitas Pengelola BUMDes Melalui Pelatihan Akuntansi Dasar dan Implementasi Aplikasi Keuangan Berbasis Web - Irfan Santiko; Zanuar Rifai; Muhamad Bintang Cakra Kencana; Lili Dwi Rakhmawaty (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to address the manual financial record-keeping problem faced by BUMDes Berkah Sentosa in Pangebatan Village, which has frequently caused data discrepancies and conflicts among its managers, while also improving the effectiveness, accountability, and cost efficiency of financial management in its food-sector business unit, and preparing financial reports that meet the requirements for funding applications, whether government subsidies, financial institution credit, or external investment. The method applied was Direct Action, through direct mentoring in the implementation of the BUMDes Financial Application (Intellectual Property Rights No. 000385898) developed by the implementation team, to address limitations in human resources for financial management. The results show an improved understanding among partners regarding financial reporting and accounting, as well as the establishment of a recording system that produces more transparent, structured, accurate, efficient, and real-time accessible financial and managerial reports, thereby supporting BUMDes in achieving better financial management.